2002
DOI: 10.1097/00007632-200201010-00029
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Intraspinal Cyst of the Cervical Spine

Abstract: Neither communication with an adjacent facet joint nor histopathology of the cyst wall provides a persuasive basis for differentiating ganglion, synovial cyst, and cyst arising from the ligaments. To accommodate the varied presentations, the authors propose a comprehensive term for these lesions: "degenerative intraspinal cyst."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 19 publications
1
67
0
1
Order By: Relevance
“…Laminectomy or hemilaminectomy without canal stenosis is usually performed to excise the cyst. 3,5,15,19) Recurrence is unlikely, even after partial excision. 5) Conservative treatment may lead to reduction in the size of cysts, using bed rest, analgesics, orthosis, and CT-guided aspiration of the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Laminectomy or hemilaminectomy without canal stenosis is usually performed to excise the cyst. 3,5,15,19) Recurrence is unlikely, even after partial excision. 5) Conservative treatment may lead to reduction in the size of cysts, using bed rest, analgesics, orthosis, and CT-guided aspiration of the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…30 Ganglion cysts, in contrast, have been called "pseudo-cysts" and are not directly connected to the joint; they have a fibrous connective tissue capsule instead of synovial tissue, and a gelatinous fluid. 56 Nonetheless, the presenting symptoms, management, and prognosis of these 2 types of lesions are the virtually the same. 23 In the spine, these cysts may occur at the juxtafacet joints, median atlantoaxial joints, atlantoocciptal joints, and/or ligamentous structures.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]6,[8][9][10][11][12]15,17,[19][20][21][22][25][26][27][28][29][30][31]33,34,36,38,39,42,43,[45][46][47][48][49][50][51][52][53][54][56][57][58][60][61][62][63][64][66][67][68][69] We also included our own 17 cases from the present study in the analysis, bringing the total number of articles to 54 and the total number of patients to 101. Ther...…”
Section: Meta-analysismentioning
confidence: 99%
“…Fewer cervical ganglion cysts than synovial cysts have been reported. To the authors' knowledge, only 14 cases of a cervical ganglion cyst have been reported [1][2][3][4][5][6][7][8][9][10][11]. Moreover, there are fewer reports of a cervical ganglion cyst arising at the C3-4 with less motion compared to other cervical joints.…”
Section: Introductionmentioning
confidence: 99%